LGG-26. TYPE II BRAF INHIBITOR TAK-580 SHOWS PROMISE FOR UPCOMING CLINAL TRIAL AS EVIDENCED BY SINGLE PATIENT IND STUDY. Issue 2 (22nd June 2018) - Wright, Karen D; Zimmerman, Mary Ann; Fine, Elizabeth; Aspri, Tristan; Kieran, Mark W; Chi, Susan
Abstract: Abnormal signaling of the RAS/RAF pathway predominates in pediatric low-grade gliomas (PLGGs). Most (85%) non-NF1 low-grade gliomas have RAS-independent BRAF activation, either due to KIAA1549:BRAF truncated fusion duplication or V600E point mutation. We previously identified two different type II BRAF inhibitors capable of inhibiting downstream activation of pERK and tumor progression in vivo for multiple point mutations and BRAF truncated fusion forms. One compound, in particular, known as TAK-580 was active on authentic human PLGG cells ex vivo and showed excellent CNS penetration. We conducted a single patient IND study for a patient with refractory, progressive LGG. Patient was initially diagnosed at age 2 years and treated with 9 different chemotherapy regimens up until age 15 years prior to starting TAK-580. Study drug was begun orally on a QOD schedule; one cycle was comprised of 28 days. Based on both tolerance and pharmacokinetic analyses, the treatment schedule and dosing were adjusted to weekly, comparable to the adult dosing schedule. MR imaging of her tumor burden has remained stable, and patient has recently started her 33 rd cycle of once weekly TAK-580. TAK-580 was well tolerated. Grade 3 and 4 likely or possibly related toxicities included acneiform rash, hyperglycemia, elevated creatinine kinase, elevated ALT and decreased phosphorus. TAK-580 posess a unique mechanism of action targeting the BRAF/MEK complex and inhibiting both BRAF point mutations and common structural abnormalities in PLGGs. These initial results support the upcoming phase I/0/II trial of TAK-580 for children with LGG and other RAS/RAF/MEK/ERK pathway activated tumors.